Financial Inclusion on the Nexus between Environmental Quality and Energy Consumption in Low-Income Sub-Saharan Africa - Olaoye, Olugbenga O.; Bowale, Ebenezer; Ewetan, Olabanji O. (International Journal of Energy Economics and Policy, 2025)
This study investigates how financial inclusion affects the connection between energy use and environmental quality in 20 low-income sub-Saharan African nations. The study employs annual secondary data from 1991 to 2022 with the cross-sectionally augmented autoregressive distributed lag (CS-ARDL) technique, which considers time dynamic, cross-sectional heterogeneity and cross-sectional dependence. The findings suggest that energy use significantly increases carbon emissions over the short- and long-terms, although financial inclusion has a positive yet statistically insignificant short-term effect on environmental quality. Furthermore, there is a positive correlation found between carbon emissions and real GDP and gross capital investment (GCI), which suggests that industrial expansion has occurred in African nations. Moreover, the study emphasizes how important financial inclusion is to sub-Saharan Africa's environmental quality. The policy recommendations urge policymakers in Sub-Saharan Africa to prioritize initiatives that enhance financial inclusion, promote green financing, support sustainable energy practices, strengthen environmental regulations, incorporate environmental considerations into economic policies, and foster regional cooperation for environmental management.